Analysis of the dynamics of performances of the russian national team in tennis (deaf sports) at the major international competitions - Al Khalili Mohaned; K.A. Ivanova; Al Khalili Sofia (Theory and Practice of Physical Culture, 2023)
The article provides an analysis of the performance of hearing-impaired Russian tennis players at the Summer Deaflympics in 2013, 2017; European Championships 2016, 2019; and World Championships 2015, 2019 in Deaf sports. In contrast to the 2013 Deaflympics, the 2015 World Cup and the 2016 European Championship, the number of countries with champions and prize-winners has increased. Our team included 8 athletes (4 male and 4 female tennis players). In total, athletes from 13 countries in 2016 and 15 countries in 2021 took part in the European Championships; 18 countries in 2015 and 22 countries in 2019 in the World Championships; and 16 countries in 2013 and 18 countries in 2017 in the Summer Deaflympics. Static analysis of the performance results of tennis players in all events at tournaments in 2013, 2015, 2016, 2017, 2019 and 2021 showed that the best results were shown at the European Championships in 2016. The players there won three gold medals out of five: two golds in singles and one gold in mixed doubles. At the World Championship in 2015, one gold medal was won.